2011
DOI: 10.1111/j.1469-8749.2011.03932.x
|View full text |Cite
|
Sign up to set email alerts
|

Function and neuroimaging in cerebral palsy: a population-based study

Abstract: AIM The aim of this population-based study was to describe function in cerebral palsy (CP) in relation to neuroimaging.METHOD Motor function, accompanying impairments, and neuroimaging (86 by magnetic resonance imaging, 74 by computed tomography) were studied in 186 children born in western Sweden between 1999 and 2002 (96 males, 90 females; age range at data collection 4-8y).RESULTS Forty per cent of the children had unilateral spastic CP, 39% bilateral, 16% dyskinetic CP, and 5% ataxia. Fifty-one per cent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
183
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(204 citation statements)
references
References 31 publications
11
183
2
8
Order By: Relevance
“…The consequence of this association can interfere with the oculomotor coordination, complex visual cognitive functions, showing a close relation between the degree of motor impairment and the extent of PVL [9][10][11] . Studies have shown that presence of epilepsy, learning difficulties and/or vision impairment correlate with the severity of motor impairment 6,12,13 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The consequence of this association can interfere with the oculomotor coordination, complex visual cognitive functions, showing a close relation between the degree of motor impairment and the extent of PVL [9][10][11] . Studies have shown that presence of epilepsy, learning difficulties and/or vision impairment correlate with the severity of motor impairment 6,12,13 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving memory in D-CP report these individuals tend to have losses 7,11,15 and the incidence of visuoperceptive, visuospatial and visuoconstructive changes is high [5][6][7][8]11,12,15 , which may interfere with the storage of information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Известно, что в 60% случаев детская неврологическая инвалидность связана с патологией перинатального периода, при этом 24% составляют пациенты с дет-ским церебральным параличом (ДЦП) [3]. По данным зарубежных авторов, заболеваемость ДЦП отмечает-ся в пределах 2,9-5 (в среднем 2,5) на 1000 детей [4,5]. В России распространенность ДЦП -2,2-3,3, в Москве -1,9 на 1000 детей.…”
unclassified